Factors Influencing Chinese International Students’ Strategic Language Learning at Ten Universities in the U.S.: A Mixed-Method Study - Yao Fu (Journal of International Students, 2018)
This QUAL-QUAN mixed-method study employed a sociocultural interpretive framework to describe the Language Learning Strategies used by Chinese international students at ten universities in the U.S. During phase one, we used typological and interpretive analysis to identify nine factors that influenced 15 students’ strategy use at four universities. In phase two we employed regression analysis to study the influence of these factors and two others on 117 students’ strategy use at six U.S. universities. While participation and English proficiency level predicted direct strategies like memory, cognitive and compensatory strategies, participation was identified as the sole predictor of indirect strategies, like metacognitive, affective and social strategies. Findings have implications for college administrators, faculty and students.